Microwave-Assisted Coprecipitation Synthesis of LaCoO3 Nanoparticles and Their Catalytic Activity for Syngas Production by Partial Oxidation of Methane - Alvarez-Galvan, Consuelo; Trunschke, Annette; Falcon, Horacio; Sanchez-Sanchez, Maricruz; Campos-Martin, Jose Miguel; Schlögl, Robert; Fierro, Jose Luis G. (Frontiers in Energy Research, 2018)
LaCoO3 perovskite-type oxides were prepared by microwave-assisted coprecipitation route and investigated in the catalytic partial oxidation of methane (CPOM) to syngas. This preparation method aims to achieve higher specific surface areas than soft-chemical methods commonly used in the preparation of engineered materials. In an attempt to accomplish the creation of mesostructured porous LaCoO3, an ionic template such as cetyl trimethyl ammonium bromide has been used as endotemplate in some samples. The influence of pH and the type of precipitating agent has been studied. The materials have been characterized at different levels: morphology has been studied by scanning electron microscopy, textural properties by nitrogen adsorption-desorption at -196ºC, structural analysis by X-ray diffraction, surface composition by X-ray photoelectron spectroscopy (XPS), thermal stability by Thermogravimetric Analysis (TGA) and carbon formation in spent catalysts, by Raman spectroscopy. Structure-activity correlations point out that the precipitating agent has a key role on the morphology and porosity of the resultant oxide, as well as on the average crystalline domain of lanthanum perovskite (catalyst precursor). Thus, the use of ammonium hydroxide as precipitant leads to materials with a higher surface area and a greater specific surface area of cobalt (per unit mass), improving their catalytic performance for the CPOM reaction. The best catalytic performance was found for the catalyst prepared using ammonium hydroxide as precipitant (pH 9) and without adding CTAB as endotemplate.